Improving Patient Advocacy in NCI Scientific Steering Committees and Task Forces. (12th May 2022) - Bangs, Rick; Lynn, Jean M; Obot, Evelyn; Osborne, Sherill; Norris, Kim
Abstract: This commentary discusses improving research advocacy as part of National Cancer Institute (NCI) clinical trial activities in scientific steering committees and task forces between 2016 and 2020. Before 2016, the focus of patient advocate input on clinical trial concept evaluation was assessing accrual feasibility. By leveraging informal benchmarking and an outside-in perspective, the NCI patient advocate steering committee, comprised of NCI scientific steering committee and task force advocates, has recalibrated research advocacy within and across its clinical trial concepts. Additionally, by focusing on research advocacy fundamentals, the NCI patient advocate steering committee clarified the scope of the research advocate roles, focused its mission, defined and developed competencies, measured engagement, and created collateral and processes that support better interactions and greater value generation. Continuous improvement in the collateral and the underlying approaches, along with calibrating their application and monitoring results, will be necessary to keep pace with the science and further enhance the value of cancer clinical trial research advocacy. The road ahead should build on these fundamentals and include increased emphasis on diversity, equity, and inclusion in clinical trial and research advocacy participants and the supporting infrastructure.